The Correlation Student Reading Speed and Reading Comprehension Achievement of The Tenth-Grade Students in Indonesia - Fahita Al Afiyah (Jurnal VARIDIKA, 2021)
The research objective was to find out the correlation between students’ reading speed and reading comprehension achievement of the tenth-grade students of MA Al Fatah Kota Mulya. The formulation of the problem in this research was “Is there any significant correlation between students’ reading speed and reading comprehension of the tenth-grade students of MA Al Fatah Kota Mulya?”. For the population, this research is from the tenth grade of MA Al Fatah Kota Mulya and contains 20 students. In here sample of the research was all of the population. Then sampling this research was done by utilizing purposive sampling. A descriptive method as a method in this research. Type instrument in this research was a test, and the test is the reading speed test and the reading comprehension achievement test. The result indicated r-obtain 0.862 higher than r-table 0.4227. So that there was a correlation between reading speed and reading comprehension achievement of the tenth-grade students of MA Al Fatah Kota Mulya or null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted.